Pravacanasara - Kundakunda ca. 7. Jh.; Jain, Dashrath 1928-; Kundakunda (Delhi Keladevi Sumatiprasad Trust, 2008)
Pravacanasara -- Rayansara -- Niyamsara
In Prakrit; translation in Hindi and English; prefatory matter in English. - Prakrit u. Hindi in Devanagari-Schr
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jainism -- Doctrines; Jaina philosophy; Salvation -- Jainism; Quelle